Entrepreneurial Interest: How The Impact of Entrepreneurship Education, Perceptions of Ease of Use on Applications in Entrepreneurial Interest - Serli; Junita Lubis; Muhammad Ali Al Ihsan (Jurnal Manajemen Bisnis, 2022)
The goal of this research was to examine how students in the Faculty of Economics and Business at the Universitas Labuhanbatu felt their exposure to entrepreneurship education influenced their desire to start their own businesses. Quantitative methods were used for this study. Using the Slovin method, this study surveyed 70 eighth-semester Management majors from the Faculty of Economics and Business at Labuhanbatu University's main campus. Interviews and questionnaires were used to gather information for this investigation. Data is analyzed with SPSS's multilinear regression function. According to this research, students at the University of Labuhanbatu's Faculty of Economics and Business who received entrepreneurship education reported a considerable increase in their enthusiasm for starting their own businesses. Partially and concurrently, application use significantly affects entrepreneurial interest, with the variables of entrepreneurial education and application ease of use each accounting for as much as 0.787 of the total R Square coefficient (R2) value. The remaining 21.3% was impacted by external variables.